(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article analyzes the role of. Music in social life, it’s significance in shaping human psychology, culture heritage, national pride and social unity. The influence of music on literature, philosophy and historical processes is examined through the ideas of great thinkers and examples from literary works. Music is evaluated as an important factor influencing human progress.